RESTful Web Services improve the efficiency of data transfer of a whole-farm simulator accessed by Android smartphones - Arroqui, Mauricio (2012)
The relentlessly increasing importance and application of Information and Communication Technologies (ICTs) in Agriculture have given birth to a new field called e-Agriculture, which focus on improving agricultural and rural development through a variety of technologies. In this sense, Agricultural Information Systems (AISs) are distributed sources of information that exploit ICTs to make agricultural processes and decision making more efficient. In order to integrate AISs and therefore build added value AISs, Web Service technologies seem to be the right path towards heterogeneous systems integration. However, there is still uncertain which is the best implementation approach to integrate Web Service-enabled AISs and mobile devices, i.e., the remote information accessors by excellence in rural areas. We comparatively explore the outcomes of employing either Simple Object Access Protocol (SOAP) or REpresentational State Transfer (REST) approaches in a Web Service-enabled whole-farm simulator accessed from Android-powered smartphones. Memory usage was 24% lower in SOAP, but even older and lower-end smartphones have enough RAM to avoid detrimental effects on performance. REST-based approaches broadly incur in less byte transferred compared to SOAP, which has huge implications on costs. That is particularly important when the Internet is accessed via GPRS or 3G protocols and pay-per-byte data plans as in most of Latin America rural areas. However, when unlimited data usage became less costly and more available in such areas, SOAP might be preferred due to the higher maturity of both the protocol and the available developer environments.